2022
DOI: 10.1002/advs.202105793
|View full text |Cite
|
Sign up to set email alerts
|

KAT6A Acetylation of SMAD3 Regulates Myeloid‐Derived Suppressor Cell Recruitment, Metastasis, and Immunotherapy in Triple‐Negative Breast Cancer

et al.

Abstract: Aberrant SMAD3 activation has been implicated as a driving event in cancer metastasis, yet the underlying mechanisms are still elusive. Here, SMAD3 is identified as a nonhistone substrate of lysine acetyltransferase 6A (KAT6A). The acetylation of SMAD3 at K20 and K117 by KAT6A promotes SMAD3 association with oncogenic chromatin modifier tripartite motif-containing 24 (TRIM24) and disrupts SMAD3 interaction with tumor suppressor TRIM33. This event in turn promotes KAT6A-acetylated H3K23-mediated recruitment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The online PROMO database showed that SMAD3 was a transcription factor binding to the SEAS1 promoter. Moreover, Yu et al [ 41 ] reported that SMAD3 acted as an oncogene in TNBC through the KAT6A acetylation-dependent regulatory mechanism. In conclusion, our data demonstrated a relationship between SMAD3, SEAS1, and miR-3940-3p in TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The online PROMO database showed that SMAD3 was a transcription factor binding to the SEAS1 promoter. Moreover, Yu et al [ 41 ] reported that SMAD3 acted as an oncogene in TNBC through the KAT6A acetylation-dependent regulatory mechanism. In conclusion, our data demonstrated a relationship between SMAD3, SEAS1, and miR-3940-3p in TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…KAT6A is also involved in triple-negative breast cancer, ovarian cancer and haematological malignancies. 2,6,19 Research has demonstrated that 51% of patients with KAT6A syndrome that have nonsense mutations also have cardiac malformations. 11 This is similar to the current case as he had ASD.…”
Section: Discussionmentioning
confidence: 99%
“… 1 It is associated with several tumours and biological processes such as leukaemia, triple-negative breast cancer, leukaemia cell proliferation, tumorigenicity and chemoresistance via acetylation epigenetics. 2 6 KAT6A protein may regulate gene transcription and a large number of protein modifications because of its modifiable lysine residues. 6 KAT6A protein plays an important role in development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3b). 139 Immune cell protein acetylation in shaping of antitumor immune responses: Protein acetylation in immune cells also regulates tumor-killing activity. STAT6 acetylation in TAMs affects their polarization and tumor-killing ability.…”
Section: Protein Acylation In Human Diseases Acetylation and Its Role...mentioning
confidence: 99%